Description of Hematological Routine in Patients Infected Covid-19 Before and After Convalence Plasma Therapy: Gambaran Hematologi Rutin Pada Pasien Terinfeksi Covid-19 Sebelum dan Sesudah Pemberian Terapi Plasma Konvalesen - Ariza, Desyani; Ferdhyanti, Andi Ulfa (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Hematological examination is very important and is often requested in several laboratories to determine the state of blood and its components. The purpose of this research is to find out the routine hematological description in patients infected with Covid-19 before and after administration of convalescent plasma therapy. The design of this study used a descriptive method with a sample population of patients infected with Covid-19 at Dr. Hospital. Wahidin Sudirohusodo. This study was followed by 17 subjects who met the inclusion criteria. Based on the results of the study, there were 6 patients who increased leukocyte examination before therapy and after therapy there were 7 patients. There were 2 patients who decreased erythrocyte examination before therapy and after therapy there were 4 patients. There were 3 patients who decreased hemoglobin before therapy and 6 patients after therapy. There was no change in the decreased hematocrit examination, namely 7 patients before and after therapy. Examination of decreased platelets before therapy there are 3 patients and after therapy 4 patients and increased platelets before therapy there are 2 patients and after therapy 3 patients. Neutrophil examination showed that there were no patients who decreased before therapy and there was 1 patient whose neutrophils decreased after therapy. For neutrophils that increased before therapy there were 9 patients and after therapy there were 7 patients. There were 10 patients who decreased lymphocyte examination before therapy and after therapy there were 9 patients. The conclusion was a change in the value of routine hematological parameters before and after convalescent plasma therapy in patients infected with Covid-19.